HAK-HAK ANAK JALANAN DI KOTA MAKASSAR : Perspektif Hukum Islam dan Hukum Positif - Ipandang, Ipandang (Program Pascasarjana, UIN Alauddin Makassar, 2014)
Artikel ini mengkaji tentang hak-hak anak jalanan perspektif hukum Islam dan hukum positif di kota Makassar. Metodologi penelitian yang digunakan adalah menggunakan pendekatan ilmu hukum dan bidang ilmu lain yang mendukung seperti pendekatan rasionalistik, fenomenologis, teologis normatif, dan sosiologis sehingga tercakup di dalamnya pendekatan multidisipliner, yang datanya merujuk pada field research. Faktor munculnya anak jalanan di kota Makassar disebabkan oleh faktor ekonomi atau kemiskinan, faktor broken-home, faktor relasi gender yang pincang, tidak adanya ruang bermain, juga karena peluang mendapatkan uang dengan mudah, urbanisasi, dan karena musiman. Hasil Penelitian menunjukkan bahwa pembinaan keluarga belum maksimal, ini dapat dilihat pada tiga aspek. Pertama, pembinaan anak jalanan dihadapkan pada lingkungan kehidupan yang tidak sesuai dengan proses pembentukan pribadi mereka. Kedua, Negara memandang semua anak sama kedudukannya dalam undang-undang, namun kelihatan bahwa anak jalanan tidak mendapatkan perhatian dan pembinaan serius.Ketiga, pembinaan anak jalanan di kota makassar menjadi tanggung jawab pemerintah, namun karena belum maksimal, maka pembinaan tersebut dilaksanakaan secara bersama dengan lembaga lain seperti Lembaga Swadaya Masyarakat (LSM). Efektivitas pemenuhan hak-hak anak jalanan perspektif hukum Islam maupun hukum positif di kota Makassar pada prinsipnya telah memenuhi aspek kemanusiaan, perlindungan HAM, dan pembinaan secara seimbang sebagaimana yang dituangkan dalam undang-undang, dan peraturan pemerintah, khususnya dalam Peraturan Daerah (Perda) Kota Makassar Nomor 2 Tahun 2008 tentang Pembinaan Anak Jalanan, Gelandangan, Pengemis dan Pengamen, namun pelaksanaannya belum efektif, dan pasal demi pasal perlu ditinjau ulang terutama pasal 47 ayat 1 dan 2, karena pasal tersebut tidak mendidik berdasarkan asas hukum keadilan, karena jumlah anak jalanan tidak dapat diminimalisir.ABSTRACTThis dissertation examines the central issue of how street children's rights perspective of Islamic law and positive law in Makassar City. As a sub-problem is how the coaching philosophy of families of street children in Makassar City, how the philosophy and principles of coaching families of children on the basis of a review of Islamic law and positive law in Makassar City, what is the factor of the emergence of street children in Makassar City and development efforts undertaken Makassar City government, how the effectiveness of the fulfillment of the rights of street children and the Islamic legal perspective positive law in Makassar City. The research methodology used in this dissertation are originated from the determination of the location and type of research, the approach based on scientific theories approach preaching and other disciplines that support such a rationalistic approach, phenomenology, normative theological, and sociological approaches to this include multidisciplinary , which refers to the field research data. Thus the data obtained mainly sourced directly from study sites and populations by taking samples. The data collection procedures through observation, interviews, questionnaires, and documentation. Processing and analysis of qualitative data and analyzed in the form of a table with the results of the data by dividing the frequency distribution. This dissertation formulates the conclusions that the problem of street children in Makassar City family coaching philosophy is based on a review do not meet the principles of the caliphate, and this can be seen in three aspects. First, the development of street children are exposed to the environment are not living according to their personal forming process. Second, the state looked at all children are equal in law, but it appears that street children are not getting the attention and coaching seriously. This is proven by the number of street children in Makassar City, which amounted to 2229. Third, development of street children is the responsibility of the government but because it is not maximized, the building in Makassar dilaksanakaan also by the Child Protection agency (LPA), Non Governmental Organizations (LSM), and the Legal Aid Institute (LBH) is jointly Makassar City Government seek guidance in terms of emphasis on maintenance and protection of street children. Factors emergence of street children in Makassar City caused economic factors or because of poverty, brokenhome factors, factors that lame gender relations, the lack of play space, as well as opportunities to earn money easily, because the suffering/ descendants of lepers, urbanization, and due to seasonal. In order to address the street children, it was a strategic move. First, an integrated coaching system ranging from household environment, society and the government of Makassar. Second, build konprehensif understanding of the position of the child in life coaching through religious, economic empowerment and skills enhancement through alternative education, cultural arts activities and others have been made by the government of Makassar. Third, the government of Makassar coordinated approach with all the elements, especially LSM, Ornop, and other observers of street children with a variety of activities that promote the development and empowerment of street children. In the meantime, the effectiveness of the fulfillment of the rights of street children as well as the perspective of Islamic law positive law in Makassar City in principle meets the humanitarian aspects, protection of human rights and development in a balanced manner as stated in the law, and government regulations, particularly Regulation (Perda) Makassar City No. 2 of 2008 on Development Street children, homeless, beggars and musician, but not yet effective implementation based on the legal principle of justice because the number of street children can not be minimized. Conclusions based on the description above, implies an understanding that the presence of street children in Makassar City is an undeniable social fact. Therefore suggested the need for a special development in an integrated and continuous. For this purpose, the government should Makassar held posts at each point as a control point ditengarahi gathering place for street children in order to develop more intensively.